Designing Gaussian basis sets to the theoretical study of the piezoelectric effect of perovskite (BaTiO3) - Treu, O.; Pinheiro, J. C.; Kondo, R. T. (Elsevier B.V., 2004)
Gaussian basis sets (24s14p, 30s19p14d, and 33s21p14d for O (P-3), Ti (S-5), and Ba (S-1) atoms, respectively), are designed with the strategy of the Generator Coordinate Hartree-Fock method. The basis sets are then contracted to [6s4p], [10s5p4d], and [16s9p5d] to O, Ti, and Ba atoms, respectively, and used in calculations of total and orbital energies of (TiO+2)-Ti-1 and (BaO)-Ba-1 fragments for quality evaluation in molecular studies. For O atom, the [6s4p] basis set is enriched with d polarization function and used along with the [10s5p4d] and [16s9p5d] basis sets for the theoretical study of the piezoelectric effect of perovskite (BaTiO3). The results of this work evidence that the piezoelectric properties in BaTiO3 can be caused by electrostatic interactions. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Gaussian basis sets; generator coordinate Hartree-Fock method; perovskite; piezoelectric effect; barium titanate